STRATEGI PENGEMBANGAN OBYEK WISATA TAMAN BEJI GRIYA WATERFALL DI DESA PUNGGUL KEC. ABIANSEMAL BADUNG BALI - Anak Agung Ngurah Gede Suindrawan; Anak Agung Bagus Wirateja; Serena Asta; Nyoman Parta (Universitas Triatma Mulya, 2023)
This research aims to identify the strengths, weaknesses, opportunities, and threats, as well as the development strategy of the Taman Beji Griya Waterfall tourism object in Punggul Village, Abiansemal Sub-district, Badung Regency, Bali. The analytical tools used are EFAS, IFAS, and SWOT analysis to formulate strategies for achieving goals based on logic to maximize strengths and opportunities while minimizing weaknesses and threats. The results of this research are as follows: Opportunities include government policies in tourism development, collaboration with local and adjacent tourist spots, government support in digitally promoting tourist destinations, the potential development of tourist spots with additional attractions, and the increasing popularity of natural and spiritual tourism. Threats include the impact of climate change and its effects on tourist attractions, public interest in other tourism object destinations, and a lack of awareness of the positive impact of natural and spiritual tourism among the community, as well as the emergence of spiritual tourism in various places in Bali. Strengths include a strategically located, easily accessible tourist spot, natural beauty and scenery, the availability of facilities such as restaurants and coffee shops, there are construction of roads or paths to the tourist park, the support and involvement of the local community, and Taman Beji Griya Waterfall as a natural and spiritual attraction. Weaknesses include ineffective promotion of tourist spots, a lack of security and comfort for tourists' belongings, ineffective management, and limitations in visitor facilities. The suitable strategy for the development of the Taman Beji Griya Waterfall tourism object in Punggul Village, Abiansemal Sub-district, Badung Regency, based on SWOT analysis, is the Strength-Opportunities strategy.